1977
DOI: 10.1007/bf00745137
|View full text |Cite
|
Sign up to set email alerts
|

The high prevalence of diabetes mellitus on a Central Pacific island

Abstract: A diabetes prevalence study on an isolated urbanized Central Pacific Island has established a prevalence rate of 34.4% in individuals aged 15 years and over. Of these, 10.4% had previously known diabetes; in the others the diagnosis was made on the basis of a plasma glucose level of at least 160 mg/100 ml 2h after a 75 gm oral glucose load. A further 11.3% of the subjects had borderline diabetes as judged by a 2-h plasma glucose of between 140 and 159 mg/100 ml. Of the diabetics, 72% had a positive family hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
3
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(102 citation statements)
references
References 18 publications
(21 reference statements)
11
86
3
2
Order By: Relevance
“…When IFG and IGT are also considered, almost one in four adult Australians has abnormal glucose tolerance. The prevalence of diabetes is similar to that reported from the U.S. (7) for nonHispanic whites (7.3% for those aged Ն20 years) but not as high as rates reported for Hispanics (7), Asian Indians (6,15), American Pima Indians (16), or Micronesian Nauruans (17). The prevalence in Australia seems to be higher than in northern Europe.…”
Section: Secular Trends: 1981 To 1999 -2000supporting
confidence: 81%
“…When IFG and IGT are also considered, almost one in four adult Australians has abnormal glucose tolerance. The prevalence of diabetes is similar to that reported from the U.S. (7) for nonHispanic whites (7.3% for those aged Ն20 years) but not as high as rates reported for Hispanics (7), Asian Indians (6,15), American Pima Indians (16), or Micronesian Nauruans (17). The prevalence in Australia seems to be higher than in northern Europe.…”
Section: Secular Trends: 1981 To 1999 -2000supporting
confidence: 81%
“…The highest diabetes prevalence rates reported in the literature (approximately 35%) are in the American Pima Indians [1] and in the Micronesian population of Nauru [2]. Prevalence rates are also quite high in a number of other American Indian populations [10,25,26], other Pacific island populations -Western Samoa [14], Tonga [27], Australian aboriginals [28], Fiji Indians [30] , certain groups in Papua New Guinea [29], and other migrant Indian communities in Singapore [22], Malaysia [31] and South Africa [32], and in the Maltese population [33].…”
Section: Prevalence Of Type 2 Diabetesmentioning
confidence: 98%
“…New Caledonia (mainland) [30] New Caledonia (Loyalty Islands) [30] Fiji [301 Prevalence rates for diabetes, based on cases of known diabetes from health interviews or national registers, almost certainly understate the true situation [14]. Screening surveys done in many diverse population groups indicate that for every known diabetic, there is at least one or two undiagnosed cases [2,21,25,32,46]. Harris has recently provided data that indicate there has been a tenfold increase in the prevalence of diabetes in the USA during the past 45 years [47].…”
Section: Type 2 Diabetes Prevalence Rates Using New Diagnostic Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…4 For example, on the Pacific island of Nauru type II diabetes was virtually unknown 50 years ago but is now present in B40% of adults. 6,7 This is the second highest prevalence recorded in the literature, after that of the Pima Indians. 3 This heightened susceptibility, however, is not equally severe across all Pacific populations and it has been suggested that the extreme susceptibility genotype was introduced by the Austronesian-speaking ancestors of present-day Polynesians, 4,8 who likely originated in Taiwan sometime before 3000 bp and reached the furthest islands of Polynesia by 800 bp.…”
Section: Introductionmentioning
confidence: 96%